2019
DOI: 10.1038/s41598-019-38507-9
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic food web structure and trophic transfer efficiency along a productivity gradient in the tropical and subtropical Atlantic Ocean

Abstract: Oligotrophic and productive areas of the ocean differ in plankton community composition and biomass transfer efficiency. Here, we describe the plankton community along a latitudinal transect in the tropical and subtropical Atlantic Ocean. Prochlorococcus dominated the autotrophic community at the surface and mixed layer of oligotrophic stations, replaced by phototrophic picoeukaryotes and Synechococcus in productive waters. Depth-integrated biomass of microzooplankton was higher than mesozooplankton at oligotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 95 publications
(71 reference statements)
3
67
0
Order By: Relevance
“…Stukel et al (2018) explained the energy transfer from the characteristic small phytoplankton (cyanobacteria) of these physical structures to zooplankton due to the role of protists as an important intermediate trophic level in these upwelling systems. Armengol et al (2019) during our cruise observed the Guinea Dome dominated by small cells (picoeukaryotes and Synechococcus), not showing a high microzooplankton biomass compared to other productive stations, but displaying relatively high autotroph growth rates at the surface layer. In any case, oceanic domes are physical structures promoting an important role of the pelagic fauna in the biological pump.…”
Section: Stationmentioning
confidence: 64%
See 2 more Smart Citations
“…Stukel et al (2018) explained the energy transfer from the characteristic small phytoplankton (cyanobacteria) of these physical structures to zooplankton due to the role of protists as an important intermediate trophic level in these upwelling systems. Armengol et al (2019) during our cruise observed the Guinea Dome dominated by small cells (picoeukaryotes and Synechococcus), not showing a high microzooplankton biomass compared to other productive stations, but displaying relatively high autotroph growth rates at the surface layer. In any case, oceanic domes are physical structures promoting an important role of the pelagic fauna in the biological pump.…”
Section: Stationmentioning
confidence: 64%
“…In the Guinea Dome, lateral transport should also be important as we sampled in the area affected by the westward motion of the cyclonic structure, probably transporting the highly productive coastal upwelled waters. In this sense, Armengol et al (2019) showed a filament-like structure affecting station 8 in their surface map of primary production during the same oceanographic cruise (see their Figure 5). Whatever the effect of zooplankton or lateral advection, in areas of high primary production large organisms are favored (e.g., Frost, 1974), as constant energy fuels their longer lives, therefore, promoting a large biomass.…”
Section: Stationmentioning
confidence: 87%
See 1 more Smart Citation
“…Dinoflagellates also include species that can form harmful algal blooms (HABs) [51], producing toxins that can have devastating effects on fisheries and aquaculture, making the research on their ecology and life cycles a priority [52]. Other heterotrophic dinoflagellates and ciliates are among the most important microzooplankton predators in the ocean, consuming between 60 and 80% of the primary production every day at a global scale [53][54][55][56]. Although the SAR supergroup dominated PIDA, our comparison of the SAR records with the Tara Oceans data [45] revealed that there are several SAR lineages, which are abundant and diverse in the marine realm, that were underrepresented when it comes to characterization of their ecological roles as interactors in aquatic environments, such as Labyrinthulomycetes and MAST (Stramenopiles), Syndiniales (MALV II; Alveolata), Acantharia, Polycystinea, and Cercozoa (Rhizaria).…”
Section: Discussionmentioning
confidence: 99%
“…The microbial loop controls most of the flow of energy and matter in subtropical gyres (Pomeroy, 1974;Azam et al, 1983;Longhurst, 1998). Picophytoplankton accounts for a large proportion of the primary productivity (Li et al, 1983), which is mostly consumed by nano-and micrograzers (Calbet and Landry, 2004;Armengol et al, 2019). Micrograzers control more than 80% of primary production in the CanCS (Arístegui et al, 2001;Marañón et al, 2007), and microzooplankton grazing has been pointed out as the principal mechanism limiting the phytoplankton growth both in artificial iron injections (Landry et al, 2000a,b;de Baar et al, 2005;Boyd et al, 2007;Henjes et al, 2007) and in dust addition experiments (Herut et al, 2005;Marañón et al, 2010).…”
Section: Introductionmentioning
confidence: 99%